2019
DOI: 10.1021/acssuschemeng.9b04290
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Recovery of Volatile Fatty Acids from Aqueous Solutions Using Terpenoids and Eutectic Solvents

Abstract: Volatile fatty acids (VFAs) are produced in the anaerobic digestion of urban or food wastes and sewage sludge. The interest in these compounds has increased because of their use as platform chemicals. In this paper, the application of natural terpenoids and eutectic solvents to sustainably recover VFAs from aqueous solutions by extraction has been evaluated. First, a screening of solvents has been done using COSMO-RS, selecting three terpenoids: geraniol, citral, and eugenol, and two hydrophobic eutectic solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…Later in 2019, two studies appeared in the literature, one by van den Bruinhorst et al [14], in which they showed that mixtures of dihexylthiourea and trioctylphosphine oxide (TOPO) are good extractors for VFAs. Another study by Rodrigues-Llorente et al [13] showed that an HDES composed of octanoic acid and thymol gave a comparable or higher extraction efficiency than organic solvents used in the literature. It should be pointed out that the three studies [13,14,22] concluded that the longer the chain of a VFA, and consequently the higher hydrophobicity, the higher the extraction efficiency.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Later in 2019, two studies appeared in the literature, one by van den Bruinhorst et al [14], in which they showed that mixtures of dihexylthiourea and trioctylphosphine oxide (TOPO) are good extractors for VFAs. Another study by Rodrigues-Llorente et al [13] showed that an HDES composed of octanoic acid and thymol gave a comparable or higher extraction efficiency than organic solvents used in the literature. It should be pointed out that the three studies [13,14,22] concluded that the longer the chain of a VFA, and consequently the higher hydrophobicity, the higher the extraction efficiency.…”
Section: Introductionmentioning
confidence: 97%
“…Another study by Rodrigues-Llorente et al [13] showed that an HDES composed of octanoic acid and thymol gave a comparable or higher extraction efficiency than organic solvents used in the literature. It should be pointed out that the three studies [13,14,22] concluded that the longer the chain of a VFA, and consequently the higher hydrophobicity, the higher the extraction efficiency. Nonetheless, the studies available in the literature only discussed the single-stage extraction of the VFAs using HDESs, without investigating the influences of key operational parameters, multistage extraction, repetitive usage of solvent, or HDES regeneration.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations